Inkarnasi Bukti Kemahakuasaan Tuhan Pada Wujud Kemanusiaan Yesus: The Incarnation as Evidence of God’s Omnipotence in the Human Nature of Jesus - Arifman Gulo; Yusak Tanasyah; Andreas Bayu Kristiantoro (Journal of Religious and Socio-Cultural, 2022)
The Incarnation is one of the Christian doctrines about the truth of God's word which is sourced from the Bible. God in His infinite omnipotence has come to earth to become a human. Man is in the form of Jesus who is God himself. He is the only begotten Son of God who became a perfect man. He is one hundred percent God, and He is one hundred percent also human. He is divine and He is also human. Through the fact of the birth and presence of Jesus in the world to do and fulfill God's will in His omnipotence, namely, to work salvation for sinners throughout the life, starting with birth (Christmas), ministry, tribulation, crucifixion, and death on the cross, resurrection, and ascending to the top. heaven. This is what is called the incarnation of God in His omnipotence. God is Spirit, but His words are real, God is real, God exists, and God is sovereign. God's sovereignty governs all things in creation, providence, and redemption. All the events that occurred in God's omnipotence in the form of Jesus while He was in the world, He has shown the reality of His humanity, His ministry, and prepared the disciples as Christian leaders to continue the ministry He had done in the form of Jesus while in the form of Jesus. world. At first glance, the kenotic model, in which the Son cedes some divine nature to incarnation, cannot help to meet this challenge, for the suggestion that the Son renounces necessary existence implies that the need in question is simply dependent and this notion is absurd. However, this study argues that some needs can be aptly described as 'dependent', subject to uncertain and changeable circumstances and that there is a natural understanding of the divine need in which the Son can give up the existence necessary to become incarnate. Inkarnasi merupakan salah satu doktrin Kristen tentang kebenaran firman Tuhan yang bersumber pada Alkitab. Allah dalam kemahakuasaan-Nya yang tidak terbatas telah turun ke dunia menjadi manusia. Manusia itu pada wujud Yesus yang adalah Allah itu sendiri. Ia adalah Anak Tunggal Allah yang menjadi manusia sempurna. Ia seratus persen Allah dan Ia seratus persen juga manusia. Ia ilahi dan Ia juga insani. Melalui fakta kelahiran dan kehadiran Yesus di dunia untuk mengerjakan dan menggenapi kehendak Allah dalam kemahakuasaan-Nya, yaitu mengerjakan keselamatan bagi orang berdosa melalui kehidupan, dimulai kelahiran (Natal), pelayanan, kesengsaraan, penyaliban dan kematian di kayu salib, kebangkitan, dan naik ke sorga. Inilah yang dinamakan inkarnasi Tuhan dalam kemahakuasaan-Nya. Tuhan itu Roh, tetapi firman-Nya nyata, Tuhan itu realitas, Tuhan itu ada, dan Tuhan itu berdaulat. Kedaulatan Tuhan mengatur segala hal di dalam ciptaan, pemeliharaan dan penebusan. Semua peristiwa yang terjadi dalam kemahakuasaan Tuhan pada wujud Yesus selama Ia berada di dunia, Ia telah menunjukkan realitas kemanusiaan-Nya, pelayanan-Nya, dan juga mempersiapkan para murid sebagai pemimpin Kristen untuk meneruskan pelayanan yang telah dikerjakan-Nya dalam wujud Yesus selama berada di dunia. Secara sepintas, model kenotik, di mana Anak menyerahkan beberapa sifat ilahi pada inkarnasi, tidak dapat membantu untuk memenuhi tantangan ini, karena saran bahwa Anak melepaskan keberadaan yang diperlukan menyiratkan bahwa kebutuhan yang dipertanyakan itu hanya bergantung dan gagasan ini tidak masuk akal. Tetapi, penelitian ini berpendapat bahwa beberapa kebutuhan dapat dengan tepat digambarkan sebagai 'bergantung', tergantung pada keadaan yang tidak pasti dan dapat berubah, dan bahwa ada pemahaman alami tentang kebutuhan ilahi di mana Anak dapat melepaskan keberadaan yang diperlukan untuk menjadi inkarnasi.